MENEBARKAN KEADILAN SOSIAL DENGAN HUKUM PROGRESIF DI ERA KOMODIFIKASI HUKUM - Shinta Dewi Rismawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
A justice is the essence of the law, but its presence is often overlooked in the name of legal certainty. These loopholes are often manipulated by parties to serve his own interests. The judge's decision is basically a representation of the legal behavior of judges in deciding cases. The judges' verdict is a legal non-sterile products of interest, so sometimes nuanced decision sharply downward and upward blunt. As a result, the practice of law becomes increasingly brighten commodity of judicial mafia practices. To cut commodity of law, the role of judges into a strategic entrance to spread spirituality progressive law in order to achieve social justice.